2013
DOI: 10.1007/978-3-642-40361-3_58
|View full text |Cite
|
Sign up to set email alerts
|

The Insignificant Role of National Culture in Global Lean Programmes

Abstract: Abstract. Large corporations are increasingly implementing lasting corporate improvement programmes based on lean thinking in their global production networks. The aim is to improve operational efficiency by sharing best operational practices and foster continuous improvement among all subsidiaries. However, it remains an open question why implementation success differs substantially across cultures and sister plants for most companies. We review the existing literature on improvement programmes and culture, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 17 publications
0
11
2
Order By: Relevance
“…This effect can be attributed to the nature of the training’s teaching methods used, for example, on-site exercises with active learning activities that provide greater interaction with study objects, as observed in Goldberg and Rank (2013), Mamat et al (2015); and Ahmad et al (2018). In addition, according to Netland et al (2012), Witt et al (2018); and Abdi et al (2018), organisations that actively implement LM by fostering knowledge management practices are more likely to have their work habits changed as LM practices are integrated into the work routine, contributing to the establishment of a learning environment across the company.…”
Section: Resultsmentioning
confidence: 99%
“…This effect can be attributed to the nature of the training’s teaching methods used, for example, on-site exercises with active learning activities that provide greater interaction with study objects, as observed in Goldberg and Rank (2013), Mamat et al (2015); and Ahmad et al (2018). In addition, according to Netland et al (2012), Witt et al (2018); and Abdi et al (2018), organisations that actively implement LM by fostering knowledge management practices are more likely to have their work habits changed as LM practices are integrated into the work routine, contributing to the establishment of a learning environment across the company.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of previous studies have found a positive relationship between LM practices and operational performance (e.g. Netland et al, 2012;Kull et al, 2014;Wiengarten et al, 2015;Onofrei et al, 2019;Iyer et al, 2019) (Shah and Ward, 2003), employee development (Challis et al, 2005), and organisational culture (Bortolotti et al, 2015;Wiengarten et al, 2015;Losonci et al, 2017).…”
Section: Lean Manufacturing and Its Impact On Operational Performancementioning
confidence: 99%
“…Finally, few studies examined the role of national culture in realising operational performance from practising LM (Netland et al, 2012;Kull et al, 2014).…”
Section: Lean Manufacturing and Its Impact On Operational Performancementioning
confidence: 99%
See 1 more Smart Citation
“…However, national culture is less and less considered to be the issue in lean. Although it took decades to demonstrate, lean has now been convincingly shown not to be exclusively “Japanese” as evidenced by the positive experience of the American Nummi (New United Motor Manufacturing, Inc.) project, the success of many other international lean organizations in all domains and the simple fact that not all organizations in Japan are lean (Krafcik, 1988; Kull et al , 2014; Netland et al , 2012).…”
Section: Introductionmentioning
confidence: 99%